Optimalisasi Good Governance dalam Meningkatkan Pengelolaan Anggaran Pemerintah ke Desa di Masa Pandemi Covid-19 (Studi Kasus Desa Bela Rakyat, Langkat) - Putri Salsa Nabila; Purnama Ramadani Silalahi (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
In order to protect the lives of the poor and easily affected by the Covid-19 outbreak, the government of the Republic of Indonesia has issued various policies. Law No. 6 of 2014 defines that the Village Fund is a fund that comes from the State Revenue and Expenditure Budget (APBN) which is submitted directly to the village which is then transferred through the district or city Regional Revenue and Expenditure Budget and will later be used to finance government administration. , implementation of development, community development, and also empowerment of rural communities. One thing that must be fulfilled in budget management is how to apply the principles of responsibility, openness, and community participation in each of these managements, so that there is continuity in the implementation of the budget. Incorrect management of village finances will have a bad impact on the village and its community. The purpose of this study was to determine the effect of good governance on the management of government budgets to villages during the Covid-19 pandemic. The type of research used in this study is a qualitative descriptive method. The data collection technique used in this research is in the form of interviews. In this study, the authors interviewed 3 informants concerned with this research. The results of this study indicate that the government has been responsible and transparent in distributing the budget during the COVID-19 pandemic to the Bela Rakyat Village. So that the village can apply the same thing, namely by transparently distributing the budget provided by the government